CHINA-ASEAN FISHERIES AND EDUCATION NETWORK PRESIDENT FORUM – A MOMENTOUS EVENT - MPRC, Pusat Media & Perhubungan Awam (USM, 2017)
PENANG, April 2017 The inaugural ChinaASEAN Fisheries and Education Network President Forum held from 11 – 13 April 2017 in Qingdao, China is yet another signal of the strong multilateral ties existing among ASEAN countries and China in the field of research and education.